Nonfarm Activities and Household Production Choices in Smallholder Agriculture in Vietnam - Huy, Nguyen Quynh (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2017)
This paper explores the effects of labour movement into nonfarm activities on household production choices in rural Vietnam. It finds that agricultural production declines and there are negative effects on farm revenue. However, these conclusions are limited in the north. Households in the north readjust their production structure by investing in livestock and other crops that require less labour. Rice farmers in the south have managed to keep their rice production unaffected by hiring more labour, and investing more capital to switch to less labour-intensive farming. The evidence of relaxing liquidity constraints is found, at least in the short run. While the decline in agricultural revenue in the north suggests some level of substitution between farming and nonfarm activities, the stability in rice production at the national level brings good news to policy makers and food security in Vietnam, despite rapid structural change over the past decades. Keywords Nonfarm, food security, rice self-sufficiency, agricultural transformation, household agricultural production References Akram-Lodhi, A.H., 2005. Vietnam’s agriculture: processes of rich peasant accumulation and mechanisms. Journal of Agrarian Change, 5(1), pp.73–116. Barrett, B., Reardon, T. and Webb, P., 2001. Nonfarm income diversification and household livelihood strategies in rural Africa: concepts, dynamics, and policy implications. Food Policy, 26, pp. 315–331. Brennan, D. et al., 2012. Rural-urban migration and Vietnamese agriculture. In Contributed paper at the 56th AARES Annual Conference. Fremantle, Western Australia. Dang, KS., Nguyen, NQ., Pham, QD., Truong, TTT. and Beresford, M 2006. Policy reform and the transformation of Vietnamese agriculture, in Rapid growth of selected Asian economies: lessons and implications for agriculture and food security, Policy Assistance Series 1/3, FAO, Bangkok. De Brauw, A., 2010. Seasonal Migration and Agricultural Production in Vietnam. Journal of Development Studies, 46(1), pp.114–139. Glewwe, P., Dollar, D. and Agrawal, N., 1994. Economic growth, poverty, and household welfare in Vietnam, World Bank, Washington, DC. Haggblade, S., Hazell, P. and Reardon, T., 2007. Transforming the rural nonfarm economy. The Johns Hopkins University Press, Baltimore, Maryland. Hazell, P. and Rahman, A., 2014. New directions for smallholder agriculture 1st ed., Oxford University Press, New York. Hoang, T.X., Pham, C.S. and Ulubaşoǧlu, M., 2014. Non-farm activity, household expenditure, and poverty reduction in rural Vietnam: 2002-2008. World Development, 64, pp.554–568. Huang, J., Wang, X. and Qiu, H.G., 2012. Small-scale farmers in China in the face of modernization and globalization, International Institute for Environment and Development/HIVOS, London. Kajisa, K., 2007. Personal networks and non-agricultural employment: the case of a farming village in the Philippines. Economic Development and Cultural Change, 55(4), pp.668–707. Kilic, T, Carletto, C, Miluka, J. and Savastano, S., 2009. Rural nonfarm income and its impact on agriculture: Evidence from Albania. Agricultural Economics, 40(2), pp.139–60. Lanjouw, J. and Lanjouw, P., 2001. The rural non-farm sector: issues and evidence from developing countries. Agricultural Economics, 26, pp.1–23. Li, L., 2013. Migration, remittances, and agricultural productivity in small farming systems in Northwest China. China Agricultural Economic Review, 5(1), pp.5–23. Minot, N., 2006. Income diversification and poverty in the Northern Uplands of Vietnam, International Food Policy Research Institute, Washington, DC. Minot, N. and Goletti, F., 1998. Export liberalization and household welfare: the case of rice in Vietnam. American Journal of Agricultural Economics, 80(4), pp.738–749. Nguyen, H.Q., 2017. Analyzing the economies of crop diversification in rural Vietnam using an input distance function. Agricultural Systems, 157, pp. 148-156. Oseni, G. and Winters, P., 2009. Rural nonfarm activities and agricultural crop production in Nigeria. Agricultural Economics, 40(2), pp.189–201. Otsuka, K., Liu, Y. and Yamauchi, F., 2013. Factor endowments, wage growth, and changing food self-sufficiency: Evidence from country-level panel data. American Journal of Agricultural Economics, 95(5), pp. 1252–1258. Pham, VH, Nguyen, TMH, Kompas, T, Che, TN. and Bui, T., 2015. Rice production, trade and the poor: regional effects of rice export policy on households in Vietnam. Journal of Agricultural Economics, 66(2), pp. 280–307. Pingali, P.L., Xuan, V.T. and Khiem, N.T., 1998. Prospects for sustaining Vietnam’s re-acquired rice export status. Food Policy, 22(4), pp. 345–358. Rozelle, S., Taylor, J.E. and DeBrauw, A., 1999. Migration, remittances, and agricultural productivity in China. American Economic Review, 89(2), pp.287–291. Stampini, M. and Davis, B., 2009. Does non-agricultural labor relax farmers’ credit constraints? Evidence from longitudinal data for Vietnam. Agricultural Economics, 40(2), pp.177–188. Taylor, J.E. and Martin, P.L., 2001. Human capital: migration and rural population change. In G. Rausser & B. Gardner, eds. Handbook of Agricultural Economics, vol 1A. New York: Elsevier Science, pp. 457–511. Taylor, J.E., Rozelle, S. and De Brauw, A., 2003. Migration and incomes in source communities: a new economic of migration perspective from China. Economic Development and Cultural Change, 52(1), pp.75–101. Taylor, J.E. and Lybbert, T., 2015. Essentials of Development Economics, University of California Press, Berkeley. Thirwall, A.P., 2006. Growth and development with special reference to developing economies 8th ed., Palgrave Macmillan, New York. van de Walle, D. and Cratty, D., 2004. Is the emerging non-farm market economy the route out of poverty in Vietnam? Economics of Transition, 12(2), pp.237–274. Warr, P., 2009. Aggregate and sectoral productivity growth in Thailand and Indonesia, Working Papers in Trade and Development, 2009/10, Arndt-Corden Department of Economics, Australian National University. Warr, P., 2014. Food insecurity and its determinants. Australian Journal of Agricultural and Resource Economics, 58(4), pp. 519-37. Weiss, C.R., 1996. Exits from a declining sector: econometric evidence from a panel of upper-Austrian farms 1980-1990, Working Paper No. 9601, Department of Economics, University of Linz. Wiggins, S, Kirsten, J. and Llambí, L., 2010. The future of small farms. World Development, 38(10), pp. 1341–48. World Bank, 2006. Vietnam: business, Development Report No 34474-VN, Hanoi, Vietnam. Keywords Nonfarm, food security, rice self-sufficiency, agricultural transformation, household agricultural production References Akram-Lodhi, A.H., 2005. Vietnam’s agriculture: processes of rich peasant accumulation and mechanisms. Journal of Agrarian Change, 5(1), pp.73–116. Barrett, B., Reardon, T. and Webb, P., 2001. Nonfarm income diversification and household livelihood strategies in rural Africa: concepts, dynamics, and policy implications. Food Policy, 26, pp. 315–331. Brennan, D. et al., 2012. Rural-urban migration and Vietnamese agriculture. In Contributed paper at the 56th AARES Annual Conference. Fremantle, Western Australia. Dang, KS., Nguyen, NQ., Pham, QD., Truong, TTT. and Beresford, M 2006. Policy reform and the transformation of Vietnamese agriculture, in Rapid growth of selected Asian economies: lessons and implications for agriculture and food security, Policy Assistance Series 1/3, FAO, Bangkok. De Brauw, A., 2010. Seasonal Migration and Agricultural Production in Vietnam. Journal of Development Studies, 46(1), pp.114–139. Glewwe, P., Dollar, D. and Agrawal, N., 1994. Economic growth, poverty, and household welfare in Vietnam, World Bank, Washington, DC. Haggblade, S., Hazell, P. and Reardon, T., 2007. Transforming the rural nonfarm economy. The Johns Hopkins University Press, Baltimore, Maryland. Hazell, P. and Rahman, A., 2014. New directions for smallholder agriculture 1st ed., Oxford University Press, New York. Hoang, T.X., Pham, C.S. and Ulubaşoǧlu, M., 2014. Non-farm activity, household expenditure, and poverty reduction in rural Vietnam: 2002-2008. World Development, 64, pp.554–568. Huang, J., Wang, X. and Qiu, H.G., 2012. Small-scale farmers in China in the face of modernization and globalization, International Institute for Environment and Development/HIVOS, London. Kajisa, K., 2007. Personal networks and non-agricultural employment: the case of a farming village in the Philippines. Economic Development and Cultural Change, 55(4), pp.668–707. Kilic, T, Carletto, C, Miluka, J. and Savastano, S., 2009. Rural nonfarm income and its impact on agriculture: Evidence from Albania. Agricultural Economics, 40(2), pp.139–60. Lanjouw, J. and Lanjouw, P., 2001. The rural non-farm sector: issues and evidence from developing countries. Agricultural Economics, 26, pp.1–23. Li, L., 2013. Migration, remittances, and agricultural productivity in small farming systems in Northwest China. China Agricultural Economic Review, 5(1), pp.5–23. Minot, N., 2006. Income diversification and poverty in the Northern Uplands of Vietnam, International Food Policy Research Institute, Washington, DC. Minot, N. and Goletti, F., 1998. Export liberalization and household welfare: the case of rice in Vietnam. American Journal of Agricultural Economics, 80(4), pp.738–749. Nguyen, H.Q., 2017. Analyzing the economies of crop diversification in rural Vietnam using an input distance function. Agricultural Systems, 157, pp. 148-156. Oseni, G. and Winters, P., 2009. Rural nonfarm activities and agricultural crop production in Nigeria. Agricultural Economics, 40(2), pp.189–201. Otsuka, K., Liu, Y. and Yamauchi, F., 2013. Factor endowments, wage growth, and changing food self-sufficiency: Evidence from country-level panel data. American Journal of Agricultural Economics, 95(5), pp. 1252–1258. Pham, VH, Nguyen, TMH, Kompas, T, Che, TN. and Bui, T., 2015. Rice production, trade and the poor: regional effects of rice export policy on households in Vietnam. Journal of Agricultural Economics, 66(2), pp. 280–307. Pingali, P.L., Xuan, V.T. and Khiem, N.T., 1998. Prospects for sustaining Vietnam’s re-acquired rice export status. Food Policy, 22(4), pp. 345–358. Rozelle, S., Taylor, J.E. and DeBrauw, A., 1999. Migration, remittances, and agricultural productivity in China. American Economic Review, 89(2), pp.287–291. Stampini, M. and Davis, B., 2009. Does non-agricultural labor relax farmers’ credit constraints? Evidence from longitudinal data for Vietnam. Agricultural Economics, 40(2), pp.177–188. Taylor, J.E. and Martin, P.L., 2001. Human capital: migration and rural population change. In G. Rausser & B. Gardner, eds. Handbook of Agricultural Economics, vol 1A. New York: Elsevier Science, pp. 457–511. Taylor, J.E., Rozelle, S. and De Brauw, A., 2003. Migration and incomes in source communities: a new economic of migration perspective from China. Economic Development and Cultural Change, 52(1), pp.75–101. Taylor, J.E. and Lybbert, T., 2015. Essentials of Development Economics, University of California Press, Berkeley. Thirwall, A.P., 2006. Growth and development with special reference to developing economies 8th ed., Palgrave Macmillan, New York. van de Walle, D. and Cratty, D., 2004. Is the emerging non-farm market economy the route out of poverty in Vietnam? Economics of Transition, 12(2), pp.237–274. Warr, P., 2009. Aggregate and sectoral productivity growth in Thailand and Indonesia, Working Papers in Trade and Development, 2009/10, Arndt-Corden Department of Economics, Australian National University. Warr, P., 2014. Food insecurity and its determinants. Australian Journal of Agricultural and Resource Economics, 58(4), pp. 519-37. Weiss, C.R., 1996. Exits from a declining sector: econometric evidence from a panel of upper-Austrian farms 1980-1990, Working Paper No. 9601, Department of Economics, University of Linz. Wiggins, S, Kirsten, J. and Llambí, L., 2010. The future of small farms. World Development, 38(10), pp. 1341–48. World Bank, 2006. Vietnam: business, Development Report No 34474-VN, Hanoi, Vietnam.